(untitled) (BioMedical Research in Medicine (BMR Medicine) (ISSN 2349-0756), 2024)
Background: Inflammation plays an important role in the initiation and progression of atherosclerosis and systemic blood markers of inflammation like white blood cell count and C-reactive protein have emerged as powerful predictor of coronary events. This study was carried out to evaluate the relationship between baseline white blood cell count and C-reactive protein with angiographic severity of coronary artery disease in patients with acute coronary syndrome and to identify those subsets of patients with acute coronary syndrome who may need to undergo invasive strategy. Method: A total of 100 patients with acute coronary syndrome including unstable angina, non-ST elevation myocardial infarction and ST elevation myocardial infarction (not thrombolysed ) were evaluated in Department of Cardiology, Sawai Man Singh Medical College & Hospital, Jaipur , Rajasthan, India with a aim to correlate baseline white blood cell count and C-reactive protein with angiographic severity of coronary artery disease. Results: This study observed that raised white blood cell count and raised C-reactive protein independently and combination of both raised white blood cell count and CRP were significantly associated with angiographic more severe coronary artery disease in form of multi vessel disease ,high stenosis score, more complex lesions and reduced TIMI flow grading. Conclusion: Raised white blood cell count and C- recactive protein in patient with acute coronary syndrome are associated with angiographic features of severe coronary artery disease. Both these markers can be used as a simpler tool for risk stratification patients with acute coronary syndrome.